2015
DOI: 10.1080/14747731.2015.1035551
|View full text |Cite
|
Sign up to set email alerts
|

After the MDGs: From Social Development to Technoenterprise in Tanzania

Abstract: This article explores how a development paradigm changes in Tanzania as the social sector concerns of the Millennium Development Goal era are practically and politically superseded by a commitment to private sector-driven structural transformation. Changes in the content and orientation of development do not occur as a result of evaluating what kinds of interventions are effective. They are the outcome of concerted efforts of paradigm reconstruction in which the role of development knowledge is pivotal. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Although Goldman (2011) (see also Goldman, 2015) has demonstrated that there exists a considerable overlap between global development institutions and speculative urbanism, international development is nonetheless comprised of a distinct set of institutional arrangements and interests which cannot simply be equated with the (global) private sector. More importantly still, in recent years scholars of development studies have observed fundamental shifts in global aid regimes which have not yet appeared in debates on African urban development (Murray and Overton, 2016;Mawdsley et al;Rampa and Bilal, 2011;Arsel and Dasgupta, 2015;Green, 2015).…”
Section: A New Era Of International Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Goldman (2011) (see also Goldman, 2015) has demonstrated that there exists a considerable overlap between global development institutions and speculative urbanism, international development is nonetheless comprised of a distinct set of institutional arrangements and interests which cannot simply be equated with the (global) private sector. More importantly still, in recent years scholars of development studies have observed fundamental shifts in global aid regimes which have not yet appeared in debates on African urban development (Murray and Overton, 2016;Mawdsley et al;Rampa and Bilal, 2011;Arsel and Dasgupta, 2015;Green, 2015).…”
Section: A New Era Of International Developmentmentioning
confidence: 99%
“…Referred to with terms such as 'retroliberalism' and 'post-aid' (Murray and Overton, 2016;Mawdsley et al;Rampa and Bilal, 2011), the characteristics of this paradigm include an increasingly overt pursuit of donor self-interest, a growing emphasis on economic and infrastructure development and increasingly hybridized public-private finance arrangements. These trends suggest that 'value for money' and 'hard' development have emerged as the new priorities of many Western donors, representing a breach with earlier MDG era concerns of donor alignment, coordination and poverty eradication (Mawdsley et al;Green, 2015). As a result, the emerging paradigm appears as a hybrid of earlier iterations, combining the global geopolitical and infrastructural agenda of the modernization era with the market predilection of the neoliberalism (Murray and Overton, 2016).…”
Section: The Netherlands As a Frontrunner Of Retroliberal Development Policymentioning
confidence: 99%
“…k Pallotti (2008). l Green, 2015 andEngström, (2018) Notes: a These were small steps and happened under the Social Democratic government and the Minister of Finance, Kjell-Olof Feldt. (Bergqvist and Lindbom, 2003).…”
mentioning
confidence: 99%
“…In a review of more than 300 articles,Freebairn (1995) found that in more than 80% of the sample both interfarm and interregional inequality increased. Moreover, removing China from the hunger statistics, the number of hungry people increased by more than 11 percent, thus suggesting that the growing food supplies were unaccompanied by growing food access(Lappé and Collins 2015).18 This idea of recreating the 'triumphant act' of philanthropy is a good example of some of the discursive powers at work in the new green revolution and contemporary privatization of development more generally(Green 2015;Moseley 2017).19 SeeDaño (2007) for details on the actors behind the Green Revolution in Africa.…”
mentioning
confidence: 99%